How does the sun make weather? - Williams, Judith (Judith A.) (Berkeley Heights, NJ : Enslow Elementary, 2005)
Presents a children's book that describes how the sun controls weather patterns and discusses why it is warmer in the summer and colder in the winter, the water cycle, and other interesting facts about the sun.
Where does weather start? -- Where does the water vapor go? -- What happens next? -- The water cycle -- Why is the weather warmer in the summer? -- How strong are the sun's rays today? -- Is there a safe way to look at the sun? -- Can the weather be too hot? -- Experiment.
Includes bibliographical references (p. 22) and index.
School Library Journal.
Horn Book.
1.7
K-3
Keywords: Sunshine -- Juvenile literature; Weather -- Juvenile literature; Sunshine; Weather; Weather; Sunshine; Weather; Sun